The Settlement Pattern of Tenganan Pegringsingan Village as an Embodiment of a Sustainable Village - Prayoga, I Made Lingga; Saraswati, A.A. Ayu Oka (Universitas Ibn Khaldun Bogor, 2024)
Tenganan Pegringsingan Village is one of the Bali Aga villages in Manggis District, Karangasem Regency, Bali, Indonesia. This village has a linear settlement pattern with the surrounding nature in the form of hills and rivers. The people in this village still uphold the traditions passed down from generation to generation by their ancestors. This village pattern is still maintained today from generation to generation. The existence of customary regulations is one of the factors in maintaining the sustainability of this village so that it can still survive under the influence of globalization. This study discusses the settlement pattern of this village as a form of sustainable village. The approach used in this study is a qualitative approach by collecting data through interviews and documentation. Data collection was carried out using tape recorders and notebooks as voice recorders, image recorders, and recording of interview results. The results of this study indicate that Tenganan Pegringsingan Village has patterns and meanings as the embodiment of a sustainable village.